Fatigue Design Evaluation of Railway Bogie with Full-Scale Fatigue Test - Jung-Won Seo; Hyun-Moo Hur; Hyun-Kyu Jun; Seok-Jin Kwon; Dong-Hyeong Lee (Advances in Materials Science and Engineering)
The bogie frame of a railway is an important structural member for the support of vehicle loading. In general, more than 25 years’ durability is necessary. Much study has been carried out in experimental and theoretical domains on the prediction of the structural integrity of the bogie frame. The objective of this paper is to estimate the structural integrity of the bogie frame of an electric railcar. Strength analysis has been performed by finite element analysis. From this analysis, stress concentration areas were investigated. To evaluate the loading conditions, dynamic stress was measured by strain gauge. It has been found that the stress and strain due to the applied loads were multiaxial conditions according to the location of the strain gauge. Fatigue strength evaluations of the bogie frame were performed to investigate the effect of a multiaxial load through the employment of a critical plane approach.